ANALISIS KINERJA KEUANGAN PADA KOPERASI UNIT DESA (KUD) KEBUN SAWIT HARAPAN DESA GABUNG MAKMUR DAN KOPERASI UNIT DESA (KUD) JAYA MAKMUR DESA KUMBARA UTAMA KABUPATEN SIAK - Nurhayati, Nurhayati; Primadayani, Syurti (Komunitas Manajemen Kompetitif, 2025)
This study aims to analyze and compare the financial performance of two Village Unit Cooperatives (KUD): KUD Kebun Sawit Harapan in Gabung Makmur Village and KUD Jaya Makmur in Kumbara Utama Village, Siak Regency, during the 2015–2017 period. The analysis employed financial ratios such as Return on Assets (ROA), Net Interest Margin (NIM), Debt to Equity Ratio (DER), and Total Asset Turn Over (TATO). The research used a quantitative descriptive method with a comparative approach, and the data analysis technique applied was the independent sample t-test. The results showed that only the DER ratio had a significant difference between the two cooperatives, while the ROA, NIM, and TATO ratios did not show any significant differences. This indicates that capital structure stability is the primary differentiator in the financial performance of the two cooperatives, whereas efficiency and profitability are relatively similar. Keywords: Financial Performance, Village Unit Cooperative, DER, ROA, NIM,